Marakka' bola as an educational vehicle for youth character values in South Sulawesi - Dewi Handayani; Arifuddin Arif; Nurliana Nurliana; Dian Sari; Roma Wijaya (Jurnal Civics: Media Kajian Kewarganegaraan)
This study explores the Marakka' Bola tradition as an educational medium to instil character values in the youth of South Sulawesi. Employing a qualitative research approach, data were gathered through observation, interviews, and documentation. The Marakka' Bola tradition, widely practised in Palakka Village, Barru District, embodies the values of unity, cooperation, and integrity. The findings reveal that the Marakka' Bola tradition is a significant cultural heritage of the Bugis community, recognised as an intangible cultural asset of Indonesia. It is a practical application of Pancasila values, particularly gotong royong (cooperation). However, the research identifies challenges, such as waning youth participation in traditional practices due to modernisation and a lack of cultural and educational significance awareness. By engaging in Marakka' Bola, participants experience a sense of togetherness and solidarity, essential for cultivating a strong societal character. This study underscores the importance of preserving ancestral traditions like Marakka' Bola, not only as a cultural identity but also as a dynamic tool for character education. The research advocates for integrating traditional practices into broader educational frameworks to address contemporary challenges in youth character development and enhance community cohesion.